Horseradish peroxidase-catalyzed oxidation of rifampicin: Reaction rate enhancement by co-oxidation with anti-inflammatory drugs - Dos Santos, Fernanda de Jesus Notário [UNESP]; Ximenes, Valdecir Farias [UNESP]; Da Fonseca, Luiz Marcos [UNESP]; De Faria Oliveira, Olga Maria Mascarenhas [UNESP]; Brunetti, Iguatemy Lourenço [UNESP] (Pharmaceutical Society of Japan, 2005)
The tuberculostatic drug rifampicin has been described as a scavenger of reactive species. Additionally, the recent demonstration that oral therapy with a complex of rifampicin and horseradish peroxidase (HRP) was more effective than rifampicin alone, in an animal model of experimental leprosy, suggested the importance of redox reactions involving rifampicin and their relevance to the mechanism of action. Hence, we studied the oxidation of rifampicin catalyzed by HRP, since this enzyme may represent the prototype of peroxidation-mediated reactions. We found that the antibiotic is efficiently oxidized and that rifampicin-quinone is the product, in a reaction dependent on both HRP and hydrogen peroxide. The steady-state kinetic constants Km app (101±23 mmol/l), Vmax app (0.78±0.09 μmol/l·s-1) and kcat (5.1±0.6 s-1) were measured (n=4). The reaction rate was increased by the addition of co-substrates such as tetramethylbenzidine, salicylic acid, 5-aminosalicylic acid and paracetamol. This effect was explained by invoking an electron-transfer mechanism by which these drugs acted as mediators of rifampicin oxidation. We suggested that this drug interaction might be important at the inflammatory site. © 2005 Pharmaceutical Society of Japan.
Keywords: Horseradish peroxidase; Paracetamol; Rifampicin; Rifampicin-quinone; Tuberculosis; antiinflammatory agent; horseradish peroxidase; hydrogen peroxide; mesalazine; paracetamol; quinone derivative; rifampicin; salicylic acid; tetramethylbenzidine; catalysis; chemical reaction; drug oxidation; electron transport; peroxidation; steady state; Animals; Anti-Inflammatory Agents; Antitubercular Agents; Catalysis; Horseradish Peroxidase; Oxidation-Reduction; Rifampin